Migrancy and Urban Memory: Immigrant Identities in In the Skin of a Lion (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In the Skin of a Lion, Michael Ondaatje reinvents the past of Toronto in the early period of the twentieth century by reconstituting the lives of forgotten immigrants, with an alternate history to the official history of the city. Ondaatje has often been criticized by observers for the application of the technique of a fragmented narrative as a method of counter-memory, of historicized archival fact combined with lyrical imagination as a way of restoring the voice of the silenced working classes. The paper analyses the idea of migrancy and the idea of urban memory based on a close analysis of the gradual political awakening of Patrick Lewis, embodied craft on the Prince Edward Viaduct, and Radical pedagogy by Alice Gull, and marginal but connected figures of Clara Dickens, Hana and Caravaggio (as well as in The English Patient). According to scholars, Ondaatje turns the city into a palimpsest, in which locations like the R. C. Harris Water Treatment Plant become mnemonic points of departure of immigrant hardship and sense of belonging. The novel brings in historical minutia and oral history as a way of revealing the fact that, socially speaking, racialized workers do not belong, even though they constructed Canada in the literal sense. The repetition of the image of skin shedding is an indication of identity as performative and translational, which is formed in the context of displacement and work. It is through such covert histories that this paper believes In the Skin of a Lion reconfigures the concept of migrancy as othering experience, but as an underpinning of urban modernity, providing an ethically charged exemplification of literary memory.